Generation of Infectious Mimivirus Virions Through Inoculation of Viral DNA Within Acanthamoeba castellanii Shows Involvement of Five Proteins, Essentially Uncharacterized - Sahmi-Bounsiar, Dehia; Baudoin, Jean-Pierre; Hannat, Sihem; Decloquement, Philippe; Chabrieres, Eric; Aherfi, Sarah; La Scola, Bernard (Frontiers in Microbiology, 2021)
One of the most curious findings associated with the discovery of Acanthamoeba polyphaga mimivirus (APMV) was the presence of many proteins and RNAs within the virion. Although some hypotheses on their role in Acanthamoeba infection have been put forward, none have been validated. In this study, we directly transfected mimivirus DNA with or without additional proteinase K treatment to extracted DNA into Acanthamoeba castellanii. In this way, it was possible to generate infectious APMV virions, but only without extra proteinase K treatment of extracted DNA. The virus genomes before and after transfection were identical. We searched for the remaining DNA-associated proteins that were digested by proteinase K and could visualize at least five putative proteins. Matrix-assisted laser desorption/ionization time-of-flight and liquid chromatography–mass spectrometry comparison with protein databases allowed the identification of four hypothetical proteins—L442, L724, L829, and R387—and putative GMC-type oxidoreductase R135. We believe that L442 plays a major role in this protein–DNA interaction. In the future, expression in vectors and then diffraction of X-rays by protein crystals could help reveal the exact structure of this protein and its precise role.